2003
DOI: 10.1016/s0009-9236(03)90475-9
|View full text |Cite
|
Sign up to set email alerts
|

An Informal Survey of Pharmacogenetics/Pharmacogenomics (PGTX) in A Sample of IND's and NDA's

Abstract: Clinical Pharmacology & Therapeutics (2003) 73, P33–P33; doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A recent internal, informal survey of the IND and NDA submissions received at the Center for Drug Evaluation and Research indicated that, of the 70 submissions with pharmacogenomic data received between 1992 and 2001, many evaluated the status of drug‐metabolizing enzymes, with CYP2D6 being the most frequent. Fig 1 depicts the distribution of submissions evaluating various polymorphic enzymes 22 . Many of the submissions received between 1992 and 1999 used phenotyping (eg, urinary metabolic ratios of dextromethorphan and dextrorphan) to estimate CYP2D6 activity.…”
Section: Applications Of Pharmacogenetics and Pharmacogenomics In Drumentioning
confidence: 99%
See 2 more Smart Citations
“…A recent internal, informal survey of the IND and NDA submissions received at the Center for Drug Evaluation and Research indicated that, of the 70 submissions with pharmacogenomic data received between 1992 and 2001, many evaluated the status of drug‐metabolizing enzymes, with CYP2D6 being the most frequent. Fig 1 depicts the distribution of submissions evaluating various polymorphic enzymes 22 . Many of the submissions received between 1992 and 1999 used phenotyping (eg, urinary metabolic ratios of dextromethorphan and dextrorphan) to estimate CYP2D6 activity.…”
Section: Applications Of Pharmacogenetics and Pharmacogenomics In Drumentioning
confidence: 99%
“…Distribution of pharmacogenetic‐pharmacogenomic studies evaluating the impact of different genotypes and phenotypes of CYP2D6, CYP2C19, CYP2C9, CYP3A, and CYP1A2 and other metabolizing enzymes, transporters, or receptors (including ABCB1 [multidrug resistance 1 ( MDR1 )] gene product P‐glycoprotein, uridine diphosphate–glucuronosyltransferase 1A1, and other transferases and proteins) on the new drug's pharmacokinetics, pharmacodynamics, or efficacy‐safety measures for 70 investigational new drugs (INDs) and new drug applications (NDAs) submitted between 1992 and 2001 22 …”
Section: Applications Of Pharmacogenetics and Pharmacogenomics In Drumentioning
confidence: 99%
See 1 more Smart Citation